ANALYSIS OF THE PRACTICE OF IMPROVING BANK SERVICES IN COMMERCIAL BANKS. - Jabborov Bakhriddin Rashidovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article scientifically and theoretically examines the importance of remote banking services in commercial banks and the possibilities for expanding their service channels. In particular, the advantages of mobile banking applications and their role in creating convenience for customers and increasing the level of use of banking services are analyzed. Furthermore, the impact of the development of remote banking services on the profitability of bank assets is evaluated based on statistical data from commercial banks of Uzbekistan.